Classical-quantum correspondence in atomic ionization by midinfrared pulses: Multiple peak and interference structures - Lemell, Christoph (2013)
Atomic ionization by strong and ultrashort laser pulses with frequencies in the midinfrared spectral region have revealed novel features such as the low-energy structures. We have performed fully three-dimensional quantum dynamical as well as classical trajectory Monte Carlo simulations for pulses with wavelengths from λ = 2000 to 6000 nm. Furthermore, we apply distorted-wave quantum approximations. This allows to explore the quantum-classical correspondence as well as the (non) perturbative character of the ionization dynamics driven by long-wavelength pulses. We observe surprisingly rich structures in the differential energy and angular momentum distribution which sensitively depend on λ , the pulse duration τ p , and the carrier-envelope phase ϕ CEP